TEORI INTERPRETASI PAUL RICOEUR DAN IMPLIKASINYA DALAM STUDI AL-QUR’AN - Mahridawati Mahridawati (STIT Darul Hijrah Martapura, 2022)
This study aims to explore the application of Paul Ricoeur's theory of interpretation within the context of Qur'anic studies. Set against the backdrop of longstanding hermeneutical debates in the study of sacred texts, Ricoeur's work, which emphasizes the dialogue between text and reader, offers a fresh perspective on traditional approaches to the exegesis of the Qur'an. Employing a qualitative approach and in-depth literary review, this research articulates Ricoeur's hermeneutic framework and identifies key elements that can be implemented in the analysis of Qur'anic texts. The findings suggest that Ricoeur's hermeneutics open up possibilities for multi-dimensional interpretation, in which the Qur'an is understood not only within the horizon of its historical context and original milieu but also within the context of the modern reader's reality. Moreover, this study highlights the potential for interfaith dialogue through the ethical and philosophical principles in Ricoeur's theory, bringing methodological renewal to Qur'anic studies and facilitating more inclusive discussions. The results of this research are expected to contribute to the development of dynamic exegesis methods and to enrich the hermeneutical discourse in contemporary Islamic studies.